2010
DOI: 10.1111/j.1399-0004.2010.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of founder mutations in BRCA1 to breast cancer in Belarus

Abstract: Mutations in the BRCA1 gene increase susceptibility to both breast and ovarian cancer. In some countries, including several in Eastern Europe, founder mutations in the BRCA1 gene are responsible for a significant proportion of breast cancer cases. To estimate the hereditary proportion of breast cancer in Belarus, we sought the presence of any of three founder mutations in BRCA1 (4153delA, 5382insC and C61G) in 500 unselected cases of breast cancer. These mutations have previously been identified in breast/ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…For high risk families of this origin, the rates of the predominant mutations in BRCA1 in the present study are 1.1% (C61G) and 0.7% (4153delA). These data are in line with data reported on non Jewish high risk families from Russia [16] Poland [14,15] and the Baltic republics [17,18]. Thus, for these unique non Jewish high risk families, these two mutations should be offered in the course of oncogenetics counseling and testing in Israel, prior to offering full mutational analysis of both genes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For high risk families of this origin, the rates of the predominant mutations in BRCA1 in the present study are 1.1% (C61G) and 0.7% (4153delA). These data are in line with data reported on non Jewish high risk families from Russia [16] Poland [14,15] and the Baltic republics [17,18]. Thus, for these unique non Jewish high risk families, these two mutations should be offered in the course of oncogenetics counseling and testing in Israel, prior to offering full mutational analysis of both genes.…”
Section: Discussionsupporting
confidence: 86%
“…A sizeable portion of these immigrants (estimated at 50%) are of Russian non Jewish origin. Two recurring mutations in BRCA1 in Russian and Baltic region high risk families have been reported: 5382InsC and 4153delA in BRCA1 [14][15][16][17][18]. In addition, the C61G is a mutation frequently detected in non Jewish Polish high risk families [14,15] and rarely in non Ashkenazi Jews [19].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the p.Cys61Gly and 5266dup BRCA1 PSVs, seem to be the most prevalent PSVs in the present study, and were reported in 11 and 16 countries, respectively. These are the most common PSVs in Poland (Górski et al, ) and other geographically related countries like Belarus (Uglanitsa et al, ). The prevalence and distribution of these PSVs in countries from the Middle East and North Africa, a region for which there is no recorded massive population exchange or North European influx is puzzling.…”
Section: Discussionmentioning
confidence: 99%
“…There appeared to be differences in the relative contribution of these mutations to breast or ovarian cancer, respectively. The high frequency of carriers may have important clinical consequences for early detection and tailored therapies to combat BRCA1 associated cancers in this population (35).…”
Section: Discussionmentioning
confidence: 99%